ANALISIS HUKUM PENYELESAIAN KETERLAMBATAN PEMBAYARAN PEMBIAYAAN AKAD MURABAHAH PADA BANK SYARIAH INDONESIA AREA PURWOKERTO (Jurnal De Jure Muhammadiyah Cirebon, 2022)
Islamic banks were born to complement the banking needs of the Indonesian people, the majority of whom are Muslim. One of the products of Islamic banks is murabahah or buying and selling which is carried out between the customer and the bank. The purpose of this research is to find out how the legal analysis and policy in the settlement of late payment of murabahah financing contract at Bank Syariah Indonesia Purwokerto area. The method in this research is using normative juridical method. The normative juridical method is carried out through literature studies that examine mainly secondary data in the form of laws and regulations, court decisions, agreements, contracts, or other legal documents, as well as research results, study results, and other references.  This research is descriptive in nature, namely providing an overview related to the settlement of late payments at Bank Syariah Indonesia Purwokerto area according to applicable law in Indonesia. In carrying out financing activities to the community, Bank Syariah Indonesia has followed or always refers to the MUI fatwa that has been issued to regulate the course of Sharia banking activities. Bank Syariah Indonesia has resolved the late payment of the murabahah contract in accordance with applicable law. Islamic banks were born to complement the banking needs of the Indonesian people, the majority of whom are Muslim. One of the products of Islamic banks is murabahah or buying and selling which is carried out between the customer and the bank. The purpose of this research is to find out how the legal analysis and policy in the settlement of late payment of murabahah financing contract at Bank Syariah Indonesia Purwokerto area. The method in this research is using normative juridical method. The normative juridical method is carried out through literature studies that examine mainly secondary data in the form of laws and regulations, court decisions, agreements, contracts, or other legal documents, as well as research results, study results, and other references.  This research is descriptive in nature, namely providing an overview related to the settlement of late payments at Bank Syariah Indonesia Purwokerto area according to applicable law in Indonesia. In carrying out financing activities to the community, Bank Syariah Indonesia has followed or always refers to the MUI fatwa that has been issued to regulate the course of Sharia banking activities. Bank Syariah Indonesia has resolved the late payment of the murabahah contract in accordance with applicable law. Keywords: late payment, financing, murabahah contract, Islamic bank